Crystal structure of the functional domain of the splicing factor Prp18 - Jiang, Jianzhong (The National Academy of Sciences, 2000)
The splicing factor Prp18 is required for the second step of pre-mRNA splicing. We have isolated and determined the crystal structure of a large fragment of the Saccharomyces cerevisiae Prp18 that lacks the N-terminal 79 amino acids. This fragment, called Prp18Δ79, is fully active in yeast splicing in vitro and includes the sequences of Prp18 that have been evolutionarily conserved. The core structure of Prp18Δ79 is compact and globular, consisting of five α-helices that adopt a novel fold that we have designated the five-helix X-bundle. The structure suggests that one face of Prp18 interacts with the splicing factor Slu7, whereas the more evolutionarily conserved amino acids in Prp18 form the opposite face. The most highly conserved region of Prp18, a nearly invariant stretch of 19 aa, forms part of a loop between two α-helices and may interact with the U5 small nuclear ribonucleoprotein particles. The structure is consistent with a model in which Prp18 forms a bridge between Slu7 and the U5 small nuclear ribonucleoprotein particles.